Economics and Law - Abdulkhasan A. M., Shpak A. S., Mashkin A. L., Gogolina E. S., Glagoleva S. V., Miasoedov C. A., Stenkina E. N., Stenkina E. N., Sakharova L. A., Sakharova L. A., Borovkova V. A., Borovkova V. A., Matasova I. I. (Economics and Law, 2020)
transit to the new model of economy, to sustainable development is complex theoretical and practical problem. It is demand to research and develop social and ecological orientation mechanisms and instruments of the financing of sustainable development. In the research indicates the modern trends of managing the financing of sustainable development; the authors made own interpretation of «mechanisms of the financing of sustainable development» (MFSD); describes the specifics and evolution of the MFSD; indicates the structure of the MFSD; present author’s classifications of the MFSD, financial instruments, financial technologies.
Keywords: устойчивое развитие; sustainable development; финансовые инструменты; механизм финансирования; финансовые технологии; институты финансирования; управление финансированием; financial mechanism; financial instruments; financial technologies; financial institution; finance management